Distributions of Breast Cancer Primary Tumor Locations in Indonesian Patients - Putri, Helenia; Kristina, Maria A.; Widjaja, Devita; Baskoro, Bernard A.; Kristiani, Erna; Muljadi, Rusli (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Introduction: Overseas studies have shown various distributions of breast cancer primary tumor locations based on stages and histopathologic types. Based on them, breast cancer was consistently reported to be found on theleft breast more than the right. Breast cancer laterality was estimated to be one of the determinant factors in prognosis. In Indonesia, there are only a few studies on the laterality of breast cancer, as well as the characteristics that accompany it. The aim of this study is to know the distributions of primary breast cancer tumor locations in Indonesian patients.Material and Methods: A cross-sectional design study was done and the data was collected from Siloam Hospital Lippo Village radiology and pathology anatomy department within the 2014-2018 period. The results were presented using descriptive statistics.Results: A total of 74 breast cancer patients from various ages and stages were enrolled in this study. Based on the histopathological types, 84.2% patients left breast tumors and 72.2% patients with right breast tumors had invasive ductal carcinoma of no special type. Based on quadrants, 50% tumors on the left breast are in the superolateral quadrant, followed by 31.6% in superomedial, 13.2% in inferomedial, and the rest in inferolateral. Conclusion: Most tumors are located in the superolateral quadrant and the most histopathological types are non-specific invasive carcinomas.